Taking Proactive Action: Introduction to the Prevention and Treatment of COVID-19 with Traditional Chinese Medicine - Jian-Nan Qiu; Hong-Yong Deng (Wolters Kluwer Health/LWW, 2021)
Since the outbreak of coronavirus disease-2019 (COVID-19), traditional Chinese medicine (TCM) has fully displayed its strength and specialty and has played an important role in the prevention and treatment of the pandemic. Faced with the unexpected development of the pandemic, the Chinese government has responded quickly and attached great importance to the effect of TCM. Comprehensive therapy integrating Chinese and Western medicine has achieved remarkable success. To summarize and introduce the prevention and treatment of COVID-19 with TCM, this article covers the perspectives of policy guideline issue, clinical diagnosis participation, and scientific research progress.